2021
DOI: 10.3832/ifor3821-014
|View full text |Cite
|
Sign up to set email alerts
|

Using nano-scale Fe0 particles and organic waste to improve the nutritional status of tree seedlings growing in heavy metal-contaminated soil

Abstract: Biogeosciences and Forestry Biogeosciences and ForestryUsing nano-scale Fe 0 particles and organic waste to improve the nutritional status of tree seedlings growing in heavy metalcontaminated soil Mahya Tafazoli (1) , Seyed Mohammad Hojjati (1) , Pourya Biparva (2) , Yahya Kooch (3) , Norbert Lamersdorf (4) The rehabilitation of heavy metal-contaminated lands is a challenging issue worldwide. The application of effective eco-friendly techniques and materials is necessary for amending the contaminated soils,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…As a result, the soil contains high amounts of stable Pb. Tafazoli et al [ 149 ] suggest that using Fe-NPs at a concentration of 3 mg/kg might effectively reduce the bioaccessibility of Pb in polluted soil and promote the development of maple seedlings. In two varieties of Vigna radiata exposed to Pb toxicity, Chen et al [ 150 ] demonstrated that Ag-NPs at 25 and 50 mg/L effectively reduced the absorption of Pb in the roots and their transfer to the leaves, thereby protecting the leaves and the photosynthesis process against Pb toxicity.…”
Section: Impacts Of Nps On Plants Under Hm Toxicitymentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, the soil contains high amounts of stable Pb. Tafazoli et al [ 149 ] suggest that using Fe-NPs at a concentration of 3 mg/kg might effectively reduce the bioaccessibility of Pb in polluted soil and promote the development of maple seedlings. In two varieties of Vigna radiata exposed to Pb toxicity, Chen et al [ 150 ] demonstrated that Ag-NPs at 25 and 50 mg/L effectively reduced the absorption of Pb in the roots and their transfer to the leaves, thereby protecting the leaves and the photosynthesis process against Pb toxicity.…”
Section: Impacts Of Nps On Plants Under Hm Toxicitymentioning
confidence: 99%
“…NPs under Pb stress enhance the absorption of nutrient elements in plants. Tafazoli et al [ 149 ] examined the impact of Fe-NPs on Acer velutinum in the event of Pb and Cd toxicity. Their findings demonstrated that Fe-NPs (1, 2, and 3 mg/kg) resulted in a growth of the levels of P, N, and K elements in the leaves.…”
Section: Impacts Of Nps On Plants Under Hm Toxicitymentioning
confidence: 99%